THE PHILOSOPHY OF ORNAMENTS IN DALEM SEGARA MADHU TEMPLE JAGARAGA VILLAGE, SAWAN DISTRICT, BULELENG REGENCY - I Made Gami Sandi Untarra; Ayu Veronika Somawati (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
One part that can be a hallmark of a temple is the carving ornament. Ornaments in sacred buildings, especially temples, of course contain very deep philosophical values. In general, the ornaments on temples, especially Pura Dalem will be related to wayang reliefs, reliefs that tell about the final journey of humans and so on. This is different from the ornaments found in the Pura Dalem Segara Madhu. The uniqueness of Pura Dalem Segara Madhu in Jagaraga Village can be seen in the reliefs located on the walls of the temples. Relief depicting the history of Balinese people against Dutch colonialism. There are also reliefs depicting ships being attacked by sea monsters, people driving cars and others. This uniqueness is a tourist attraction for people to visit the temple. The uniqueness of the ornaments owned by Pura Dalem Segara Madhu, Jagaraga Village, becomes an interesting thing to study with regard to the philosophical values ​​contained in it. By using a qualitative descriptive method, this paper examines the philosophy of ornamentation in the Pura Dalem Segara Madhu. The results of the study are that ornament is a work that is produced in addition to relating to the beauty that is captured by the human senses, it is also related to the values ​​of truth and virtue in the teachings of Hinduism. In addition, it can be understood that all the reliefs contained in the Pura Dalem Segara Madhu Jagaraga are related to each other regarding the struggle of the people of Jagaraga Village. This reaffirms that this temple is not only related to the spiritual life of the community, but also relates to the history of the struggle of the community which is the spirit of social life.